Vaccine-Mediated Induction of an Ebolavirus Cross-Species Antibody Binding to Conserved Epitopes on the Glycoprotein Heptad Repeat 2/Membrane-Proximal External Junction. (22nd August 2018) - Cagigi, Alberto; Ploquin, Aurélie; Niezold, Thomas; Zhou, Yan; Tsybovsky, Yaroslav; Misasi, John; Sullivan, Nancy J
Abstract: The membrane-proximal external regions (MPER) of the human immunodeficiency virus envelope glycoprotein (GP) generate broadly reactive antibody responses and are the focus of vaccine development efforts. The conservation of amino acids within filovirus GP heptad repeat region (HR)2/MPER suggests that it may also represent a target for a pan-filovirus vaccine. We immunized a cynomolgus macaque against Ebola virus (EBOV) using a deoxyribonucleic acid/adenovirus 5 prime/boost strategy, sequenced memory B-cell receptors, and tested the antibodies for functional activity against EBOV GP. Antibody ma-C10 bound to GP with an affinity of 48 nM and was capable of inducing antibody-dependent cellular cytotoxicity. Three-dimensional reconstruction of single-particle, negative-stained, electron microscopy showed that ma-C10 bound to the HR2/MPER, and enzyme-linked immunosorbent assay reveals it binds to residues 621–631. More importantly, ma-C10 was found to bind to the GP of the 3 most clinically relevant Ebolavirus species, suggesting that a cross-species immunogen strategy targeting the residues in this region may be a feasible approach for producing a pan-filovirus vaccine.